Porous polymers - Silverstein, Michael S.; Cameron, Neil R. (Neil Ronald), 1969-; Hillmyer, Marc A. (Hoboken, N.J. : Wiley, 2011)
This book gathers the various aspects of the porous polymer field into one volume. It not only presents a fundamental description of the field, but also describes the state of the art for such materials and provides a glimpse into the future. Emphasizing a different aspect of the ongoing research and development in porous polymers, the book is divided into three sections: Synthesis, Characterization, and Applications. The first part of each chapter presents the basic scientific and engineering principles underlying the topic, while the second part presents the state of the art results bas.
Section 1. Synthesis -- section 2. Characterization -- section 3. Applications.
Includes bibliographical references and index.
Keywords: Porous materials; Plastic foams; TECHNOLOGY & ENGINEERING -- Material Science; Plastic foams; Porous materials; Electronic books